2015
DOI: 10.1016/j.pscychresns.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithm accurately detects fMRI signature of vulnerability to major depression

Abstract: Standard functional magnetic resonance imaging (fMRI) analyses cannot assess the potential of a neuroimaging signature as a biomarker to predict individual vulnerability to major depression (MD). Here, we use machine learning for the first time to address this question. Using a recently identified neural signature of guilt-selective functional disconnection, the classification algorithm was able to distinguish remitted MD from control participants with 78.3% accuracy. This demonstrates the high potential of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 15 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…In addition, brain representations relevant for performance and clinical outcomes may often be distributed across multiple regions and networks. If so, models that integrate contributions from different brain areas will likely be required for accurate prediction 24,58,135 .…”
Section: Future Directions: Toward a Next Generation Of Translationalmentioning
confidence: 99%
“…In addition, brain representations relevant for performance and clinical outcomes may often be distributed across multiple regions and networks. If so, models that integrate contributions from different brain areas will likely be required for accurate prediction 24,58,135 .…”
Section: Future Directions: Toward a Next Generation Of Translationalmentioning
confidence: 99%
“…Researchers have discovered disruptions of FCN in neuropsychiatric diseases, such as Alzheimer's disease (Greicius, Srivastava, Reiss, & Menon, ; Wang et al, ), mild cognitive impair (MCI) (Bai et al, ; Das et al, ), depression (Greicius et al, ; Yang et al, ), autism spectrum disorder (ASD) (Anderson et al, ; Assaf et al, ; Cheng, Rolls, Gu, Zhang, & Feng, ; Ebisch et al, ), and schizophrenia (Wang, Xia, et al, ). On the other hand, machine learning techniques have been proven to be very effective in identifying biomarkers for brain disease diagnosis based on FCN (Chen, Zhang, et al, ; Jiang, Zhang, & Zhu, ; Khazaee, Ebrahimzadeh & Babajani‐Feremi, ; Sato et al, ; Wee, Yap, Zhang, Wang, & Shen, ; Zhang, Hu, Ma, & Xu, ). Here, we focus on exploring biomarkers from FCN for ASD diagnosis using state‐of‐the‐art machine learning techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies are often limited by focus on single biomarkers or other predictors as a basis for intervention allocation. However, we need more advanced statistical modeling techniques, such as machine learning (Sato et al, 2015 ), and should aim to translate identified disease mechanisms into molecular blood-based biomarker combinations (e.g., Chan et al, 2014 ) to combine different biological variables to predict disorder vulnerability and treatment responses. At the same time, the need for innovative pilot studies in single centers to develop and test novel hypotheses remains.…”
Section: Methodological Challenges and Directionsmentioning
confidence: 99%